Fixed-income portfolio optimization based on dynamic Nelson-Siegel models with macroeconomic factors for the Brazilian yield curve - Schnorrenberger, Richard (2017)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Sócio-Econômico, Programa de Pós-Graduação em Economia, Florianópolis, 2017.